Polyoxidovanadates [MoVIVV9O28]5- and [H2PtIVVV9O28]5- interact with CHO cell plasma membrane lipids causing aggregation and activation of a G protein-coupled receptor - Kostenkova, Kateryna; Althumairy, Duaa; Rajan, Ananthu; Kortz, Ulrich; Barisas, B. George; Roess, Deborah A.; Crans, Debbie C. (Frontiers in Chemical Biology, 2023)
Mono-substituted heteropolyoxidovanadates, when compared to effects of a corresponding isopolyoxidovanadate (POV), were found to be more effective initiators of signal transduction by a G protein-coupled receptor (GPCR), specifically the luteinizing hormone receptor (LHR). Here we report that LHRs signal productively when CHO cells expressing the receptor are treated with two heteropolyoxidovanadates PtIV in monoplatino(IV)nonavanadate(V) ([H2PtIVVV9O28]5-, V9Pt), and MoIV in monomolybdo(VI)-nonavanadate(V) ([MoVIVV9O28]5-, V9Mo). Both substituted decavanadate derivatives were more effective than decavanadate which is both more charged and has greater stability and which forms the V10O286- anion (V10) in cell culture medium at pH 7.4. For viable CHO cells expressing 10k or 32k LHR/cell and treated with 11 M V9Pt and 13 M V9Mo, mono-substituted heteropolyoxidovanadates significantly decreased the packing of plasma membrane lipids for about 1 hr. This brief change in membrane structure was accompanied by increased aggregation of LHR and cell signaling as indicated by increased intracellular levels of cAMP. More pronounced changes in lipid packing and LHR signaling were associated with short acting heteropolyoxidovanadates than the more stable V10. When LHR was overexpressed, V9Pt and V9Mo had little or no effect on membrane lipid packing or receptor aggregation and the LHR was constitutively activated as indicated by elevated intracellular cAMP levels. Speciation of V9Pt and V9Mo in H2O and cell medium was monitored using 51V NMR spectroscopy and confirmed that V9Pt and V9Mo had greater effects on CHO cells despite decomposing more rapidly in the cell growth medium. Thus, under conditions that promote CHO cell growth, V9Pt and V9Mo, despite their smaller molecular charge and their reduced stability, favor LHR signaling over that induced by V10. Importantly, under the same experimental conditions, CHO cells treated with V9Pt and V9Mo are not exposed to toxic effects observed for cells treated with the longer lived V10. In summary, unlike the longer lived V10 which is comparatively toxic to cells, monosubstituted heteropolyoxidovanadates are more effective in transiently initiating signaling by a G protein-coupled receptor but, because of rapid hydrolysis, do not inhibit cell growth.